1997
DOI: 10.1016/s0886-3350(97)80149-6
|View full text |Cite
|
Sign up to set email alerts
|

Laser in situ keratomileusis to treat myopia: Early experience

Abstract: With limitations, LASIK could be considered as a treatment for moderate and high myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(27 citation statements)
references
References 29 publications
0
22
0
5
Order By: Relevance
“…Alterações endoteliais após LASIK têm sido estudadas (4)(5)(6)(7) . Alguns autores (4) acreditam que a perda endotelial de até 4,11% relativa à quantidade de correção programada foi causada, provavelmente, pelas ondas de choque da fotoablação e pela manipulação corneana durante a ceratomileusis.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Alterações endoteliais após LASIK têm sido estudadas (4)(5)(6)(7) . Alguns autores (4) acreditam que a perda endotelial de até 4,11% relativa à quantidade de correção programada foi causada, provavelmente, pelas ondas de choque da fotoablação e pela manipulação corneana durante a ceratomileusis.…”
Section: Discussionunclassified
“…A redução substancial encontrada na paquimetria foi semelhante àquela encontrada em estudos para correção de erros refracionais semelhantes em adultos (5) . É difícil comparar este grupo heterogêneo de pacientes tão jovens, com outros grupos descritos na literatura.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…LASIK for myopia appears to result in good refractive outcomes with individual excimer laser types; [1][2][3][4][5] however, comparative studies for different excimer lasers have not been reported. This paper aims to compare refractive results obtained using the Technolas 217 Planoscan (Bausch & Lomb Surgical, CA, USA) and the NIDEK EC-5000 (NIDEK Co., Gamagori, Japan) excimer lasers for uncomplicated myopic refractive corrections.…”
Section: Introductionmentioning
confidence: 99%